Summary of the Republican Science and Practice Conference "Technological education in context of modernization of educational system in the Republic of Tuva”, Kyzyl, 12 April 2013 - ., . . (The New Research of Tuva, 2013)
Summary of the Republican Science and Practice Conference "Technological education in context of modernization of educational system in the Republic of Tuva”, Kyzyl, 12 April 2013
Keywords: conference-2013; Kyzyl; problems of education; technology